[-6-(-9+2)+(-5+8)]-[-2+6-(-6+8)]
mondocvasile:
eu as vrea si rezolvareaa
Răspunsuri la întrebare
Răspuns de
0
[-6-(-9+2)+(-5+8)]-[-2+6-(-6+8)] =
(-6 + 9 - 2 -5 +8) - (-2 + 6 +6 -8 ) =
4 - 2 =
2
(-6 + 9 - 2 -5 +8) - (-2 + 6 +6 -8 ) =
4 - 2 =
2
Răspuns de
0
[-6-(-9+2)+(-5+8)]-[-2+6-(-6+8)]=
[-6-(-7)+(+3)]-[4-(+2)]=
(-6+7+3)-(4-2)=
(1+3)-2=
4-2=
2
[-6-(-7)+(+3)]-[4-(+2)]=
(-6+7+3)-(4-2)=
(1+3)-2=
4-2=
2
Alte întrebări interesante
Istorie,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Ed. tehnologică,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă